2003
DOI: 10.1163/15685620360511137
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo degradation studies of a novel linear copolymer of lactide and ethylphosphate

Abstract: Poly(lactide-co-ethylphosphate)s, a new class of linear phosphorus-containing copolymers made by chain-extending low-molecular-weight polylactide prepolymers with ethyl dichlorophosphate, were investigated for their in vitro and in vivo degradation mechanism and kinetics. Microspheres made from poly(lactide-co-ethylphosphate) were studied under both accelerated and normal in vitro degradation conditions. Gel permeation chromatography (GPC), 1H- and 31P-NMR, weight loss measurements, and differential scanning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Species I appears to be formed as a result of hydrolysis of the phosphate-[1,4-bis(hydroxyethyl)terephthalate] bond (route 1 in Scheme 3) and the phosphate--ethoxy bond (route 2 in Scheme 3) in the PPE. Similar degradation pathways have been reported for poly(lactide-co-ethylphosphate) [22]. The peak observed at m/z 581.1436 (m/z calc 581.1424) corresponds to the loss of a water molecule from I.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Species I appears to be formed as a result of hydrolysis of the phosphate-[1,4-bis(hydroxyethyl)terephthalate] bond (route 1 in Scheme 3) and the phosphate--ethoxy bond (route 2 in Scheme 3) in the PPE. Similar degradation pathways have been reported for poly(lactide-co-ethylphosphate) [22]. The peak observed at m/z 581.1436 (m/z calc 581.1424) corresponds to the loss of a water molecule from I.…”
Section: Resultssupporting
confidence: 75%
“…Zhao and coworkers studied the in vitro and in vivo degradation of a poly(lactide-coethylphosphate) copolymer, the bulk of which was PDLA [poly(D,L-lactide)], using gel permeation chromatography, 1 H and 31 P NMR weight loss measure-ments, and differential scanning calorimetry [22]. Their results indicated a two stage degradation of the PPE: In the first (fast) stage, degradation predominantly occurs at the phosphate-lactide bonds with minor degradation at phosphate-ethoxy bonds.…”
mentioning
confidence: 99%
“…As stated below, in regard to the triblock copolymer of PLLA and poly(ethylene oxide) (PEO) (abbreviated as PLLA-b-PEO-b-PLLA), the ester groups connecting PLLA and PEO rather than those connecting the lactyl units were preferentially hydrolytically degraded at an early stage. Chaubal et al [217] showed that in the NHD of poly(DLlactide)-b-poly(ethylphosphate) (PDLLA-b-PEP), the cleavage of the ethylphosphate-lactyl linkage first occurs and then Solid [17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Solid (crystalline residues) [41,42] Solid (porous) [43] Ringer solution Solid (including fibers) [44][45][46] Simulated body fluid Solid [ [57] HCl solution, DL-lactic acid solution (pH 2.0) Solid [58] HCl solution (pH À0.9, 0.2), NaOH solution (pH 11.8, 12 Solid [190] PLLA-PCL multiblock copolymer Not specified Phosphate-buffered solution Solid [191] PLLA-b-poly(1,5-dioxepan-2-one)-b-PLLA and multiblock copolymer 37 Phosphate-buffered solution (pH 7.4) Solid [192,193] (continued ) the cleavage of the lactyl-lactyl linkage takes place. For this reason, the hydrolytic degradation of PLLA-b-PEO-b-PLLA and PDLLA-b-PEP was faster at an early stage than at a late stage.…”
Section: Molecular Degradation Mechanismmentioning
confidence: 99%
“…48,86 HPLC and MS techniques have been successfully used on the isolation and identification of the degradation products of biodegradation of polyurethanes by cholesterol esterase. 50,56,57 Chaubal and coworkers 69 followed the generation of water-soluble degradation products during the in vitro degradation of a linear copolymer of lactide and ethylphosphate by NMR.…”
Section: Isolation and Identification Of Degradation Productsmentioning
confidence: 99%